The functional role of xylem parenchyma cells and aquaporins during recovery from severe water stress. (26th October 2016) - Secchi, Francesca; Pagliarani, Chiara; Zwieniecki, Maciej A.
Abstract: Xylem parenchyma cells [vessel associated cells (VACs)] constitute a significant fraction of the xylem in woody plants. These cells are often closely connected with xylem vessels or tracheids via simple pores (remnants of plasmodesmata fields). The close contact and biological activity of VACs during times of severe water stress and recovery from stress suggest that they are involved in the maintenance of xylem transport capacity and responsible for the restoration of vessel/tracheid functionality following embolism events. As recovery from embolism requires the transport of water across xylem parenchyma cell membranes, an understanding of stem‐specific aquaporin expression patterns, localization and activity is a crucial part of any biological model dealing with embolism recovery processes in woody plants. In this review, we provide a short overview of xylem parenchyma cell biology with a special focus on aquaporins. In particular we address their distributions and activity during the development of drought stress, during the formation of embolism and the subsequent recovery from stress that may result in refilling. Complemented by the current biological model of parenchyma cell function during recovery from stress, this overview highlights recent breakthroughs on the unique ability of long‐lived perennial plants to undergo cycles of embolism‐recovery related to drought/rewetting or freeze/thaw events.